Sex Differences in the Physiological Response to Ethanol of Rat Basolateral Amygdala Neurons Following Single-Prolonged Stress - Ornelas, Laura C.; Keele, N. B. (Frontiers in Cellular Neuroscience, 2018)
Females are more likely to develop post-traumatic stress disorder (PTSD) than males. Also, symptoms of PTSD frequently precede alcohol abuse in females. Stressful, threat-related stimuli are evaluated by the amygdala, which is critical for establishing the emotional salience of environmental stimuli. Ethanol and stress have been shown to modify amygdala excitability, but effects of acute ethanol on neurons of the basolateral amygdala (BLA) in both males and females exposed to stress is unknown. The purpose of this study is to determine stress-induced changes in membrane properties of BLA neurons and to determine how ethanol modulates these changes in male and female rats. Whole-cell recordings were obtained from BLA neurons of both male and female rats exposed to single-prolonged stress (SPS). Neuronal excitability, quantified as the number of action potentials, was determined in current clamp mode by applying a series of depolarizing current steps. Hyperpolarization-activated current (Ih) was elicited in voltage clamp. Excitability and Ih amplitude were determined before and during the superfusion of ethanol (EtOH; 30mM) in BLA neurons from SPS-treated male and female rats. SPS alone did not alter the firing properties of BLA neurons from either males or females. However, following SPS, BLA neurons from males and females respond differently to ethanol. Superfusion of EtOH (30 mM) inhibited spike firing in BLA neurons from rats exposed to SPS, and EtOH-induced inhibition was greater in females than in males exposed to stress. Also, EtOH (30mM) selectively decreased Ih amplitude in BLA neurons from SPS-treated male rats from 171 ± 46 pA in (pre-EtOH) control to 53 ± 51 pA in the presence of EtOH (30 mM). EtOH did not reduce Ih in BLA neurons from SPS-treated females. Together, these suggest important sex differences in the physiological responses to EtOH in stress disorders such as PTSD, that have high comorbidity with alcohol use disorders.